Properties of cationic monosubstituted tetraalkylammonium cyclodextrin derivatives – their stability, complexation ability in solution or when deposited on solid anionic surface - Popr, Martin; Filippov, Sergey K.; Matushkin, Nikolai; Dian, Juraj; Jindřich, Jindřich (Beilstein Journal of Organic Chemistry, 2015)
The thermal stability of the monosubstituted cationic cyclodextrin (CD) derivatives PEMEDA-β-CD and PEMPDA-β-CD, which differ in their substituent linker length (ethylene and propylene, respectively), was studied via 1H NMR experiments. PEMPDA-β-CD exhibited higher resistance towards the Hofmann degradation and was chosen as a more suitable host molecule for further studies. Inclusion properties of PEMPDA-β-CD in solution with a series of simple aromatic guests (salicylic acid, p-methoxyphenol and p-nitroaniline) were determined by isothermal titration calorimetry (ITC) and compared to the native β-CD. Permanently charged cationic CD derivatives were successfully deposited on the anionic solid surface of polymeric Nafion® 117 membrane via electrostatic interactions. Deposition kinetics and coverage of the surface were determined by ELSD. Finally, the ability of the CD derivatives bound to the solid surface to encapsulate aromatic compounds from aqueous solution was measured by UV–vis spectroscopy. The obtained results are promising for future industrial applications of the monosubstituted β-CD derivatives, because the preparation of cationic CD derivatives is applicable in large scale, without the need of chromatographic purification. Their ionic deposition on a solid surface is simple, yet robust and a straightforward process as well.
Keywords: cyclodextrins; inclusion properties; solid surface; tetraalkylammonium derivatives; thermal stability

(untitled) - Villiers, A. (C. R. Hebd. Seances Acad. Sci., 1891)

(untitled) - Szejtli, J. (Chem. Rev., 1998)

(untitled) - Szejtli, J. (J. Inclusion Phenom. Mol. Recognit. Chem., 1992)

(untitled) - Laza-Knoerr, A. L.; Gref, R.; Couvreur, P. (J. Drug Targeting, 2010)

(untitled) - Popr, M.; Hybelbauerová, S.; Jindřich, J. (Beilstein J. Org. Chem., 2014)

(untitled) - Khan, A. R.; Forgo, P.; Stine, K. J.; D’Souza, V. T. (Chem. Rev., 1998)

(untitled) - Binkowski, C.; Hapiot, F.; Lequart, V.; Martin, P.; Monflier, E. (Org. Biomol. Chem., 2005)

(untitled) - Cucinotta, V.; Contino, A.; Giuffrida, A.; Maccarrone, G.; Messina, M. (J. Chromatogr., A, 2010)

(untitled) - Cai, H.; Nguyen, T. V.; Vigh, G. (Anal. Chem., 1998)

(untitled) - Mikuš, P.; Kaniansky, D. (Anal. Lett., 2007)

(untitled) - Tang, W.; Muderawan, I. W.; Ong, T.-T.; Ng, S.-C. (Tetrahedron: Asymmetry, 2007)

(untitled) - Chankvetadze, B.; Endresz, G.; Blaschke, G. (Chem. Soc. Rev., 1996)

(untitled) - Matsui, Y.; Ogawa, K.; Mikami, S.; Yoshimoto, M.; Mochida, K. (Bull. Chem. Soc. Jpn., 1987)

(untitled) - Matsui, Y.; Okimoto, A. (Bull. Chem. Soc. Jpn., 1978)

(untitled) - Sueur, B.; Leclercq, L.; Sauthier, M.; Castanet, Y.; Mortreux, A.; Bricout, H.; Tilloy, S.; Monflier, E. (Chem. – Eur. J., 2005)

(untitled) - Nelles, G.; Weisser, M.; Back, R.; Wohlfart, P.; Wenz, G.; Mittler-Neher, S. (J. Am. Chem. Soc., 1996)

(untitled) - Weisser, M.; Nelles, G.; Wohlfart, P.; Wenz, G.; Mittler-Neher, S. (J. Phys. Chem., 1996)

(untitled) - Henke, C.; Steinem, C.; Janshoff, A.; Steffan, G.; Luftmann, H.; Sieber, M.; Galla, H.-J. (Anal. Chem., 1996)

(untitled) - Fragoso, A.; Caballero, J.; Almirall, E.; Villalonga, R.; Cao, R. (Langmuir, 2002)

(untitled) - Lee, J.-Y.; Park, S.-M. (J. Phys. Chem. B, 1998)

(untitled) - Auletta, T.; Dordi, B.; Mulder, A.; Sartori, A.; Onclin, S.; Bruinink, C. M.; Péter, M.; Nijhuis, C. A.; Beijleveld, H.; Schönherr, H.; Vancso, G. J.; Casnati, A.; et al. (Angew. Chem., 2004)

(untitled) - Yang, X.; Shi, J.; Johnson, S.; Swanson, B. (Sens. Actuators, B, 1997)

(untitled) - Busse, S.; DePaoli, M.; Wenz, G.; Mittler, S. (Sens. Actuators, B, 2001)

(untitled) - Grossi, N.; Espuche, E.; Escoubes, M. (Sep. Purif. Technol., 2001)

(untitled) - Kusumocahyo, S. P.; Sumaru, K.; Kanamori, T.; Iwatsubo, T.; Shinbo, T. (J. Membr. Sci., 2004)

(untitled) - Yang, Y.; Yang, X.; Liu, Y.-L.; Liu, Z.-M.; Yang, H.-F.; Shen, G.-L.; Yu, R.-Q. (J. Photochem. Photobiol., A, 2005)

(untitled) - Willerich, I.; Schindler, T.; Ritter, H.; Gröhn, F. (Soft Matter, 2011)

(untitled) - Faul, C. F. J.; Antonietti, M. (Adv. Mater., 2003)

(untitled) - Antonietti, M.; Conrad, J.; Thuenemann, A. (Macromolecules, 1994)

(untitled) - Tieke, B.; El-Hashani, A.; Toutianoush, A.; Fendt, A. (Thin Solid Films, 2008)

(untitled) - Cope, A. C.; Mehta, A. S. (J. Am. Chem. Soc., 1963)

(untitled) - Höfler, T.; Wenz, G. (J. Inclusion Phenom. Mol. Recognit. Chem., 1996)

Biophysical Tools for Biologists, Volume One: In Vitro Techniques - Freyer, M. W.; Lewis, E. A. (Isothermal Titration Calorimetry: Experimental Design, Data Analysis, and Probing Macromolecule/Ligand Binding and Kinetic Interactions, 2008)

(untitled) - Fielding, L. (Tetrahedron, 2000)

(untitled) - Hirose, K. (J. Inclusion Phenom. Macrocyclic Chem., 2001)

(untitled) - Junquera, E.; Peña, L.; Aicart, E. (J. Pharm. Sci., 1998)

(untitled) - Junquera, E.; Ruiz, D.; Aicart, E. (J. Colloid Interface Sci., 1999)

(untitled) - Sueishi, Y.; Miyakawa, T. (J. Phys. Org. Chem., 1999)

(untitled) - Buvári, A.; Barcza, L. (J. Chem. Soc., Perkin Trans. 2, 1988)

(untitled) - Kuroda, Y.; Yamada, M.; Tabushi, I. (J. Chem. Soc., Perkin Trans. 2, 1989)